The East Asian welfare model : welfare Orientalism and the state - Goodman, Roger, 1960-; White, Gordon, 1942-; Kwon, Huck-ju (ESRC Pacific Asia Programme (Series), 1998)
Offers the first broad-ranging study of the development and implementation of various welfare systems in East Asia, unfolding the reality behind the rhetoric in this important area.